Formação continuada em Jornada Especial Integral (JEIF), nas visões de professores e coordenação pedagógica de curso de Magistério no Ensino Médio da EMEFM Derville Alegretti - Moreira, Diego (2022)
This research, based on bibliographic and documentary studies and empirical research, seeks to identify, in the municipal high school Derville Allegretti, specifically in the relationships that take place in the Teaching Course, the conceptions, the trajectories of training and professionalization, the training processes, the systematizations, perceptions and conceptions of training and professional development. It also seeks to identify how the pedagogical coordinator plans, researches, performs, monitors and evaluates the training processes carried out in schools during collective working hours (JEIFs). The focus of the investigation is to understand the processes of training and professional development of teachers and pedagogical coordination, in addition to investigating how the relationship with continuing education can transform and characterize teaching activity, considering the singularities for the Teaching Course. This is a qualitative research, which was carried out considering the views expressed by a coordinator and the 12 (twelve) teachers of the Teaching Course on the different ways they relate to school, training and professionalization, and such data were collected through questionnaires and interviews. Specific institutional documents - Laws, Decrees and Resolutions - that express the structure, attributions and expectations for the coordinator's performance and for the moment of training are also analyzed. The research guides the hypothesis that the pedagogical coordinator has specific knowledge to carry out the trainings, considering the nature of the course offered; that the time of the training deals with specific issues for the formation of teaching; that the nature and systematization of the knowledge produced there may or may not have a direct relationship with the guiding documents of the Secretariat of Education; and that this the high school student Authors such as Francisco Imbernón, Antonio Nóvoa and Alda Junqueira Marin provide theoretical support for the research